Nurses' attitudes towards the implementation of the Mother-Baby Friendly Initiative in selected primary healthcare facilities at Makhuduthamaga Municipality, Limpopo province - Siyabulela E. Mgolozeli; Hilda N. Shilubane; Lunic B. Khoza (AOSIS, 2019)
Background: The implementation of the Mother-Baby Friendly Initiative (MBFI) strategy demonstrated its capabilities to improve global children's health and maternal survival. However, its implementation in primary healthcare (PHC) facilities remains a challenge as many nurses are reluctant to adopt it for the improvement of child and maternal healthcare services in their respective clinics. Objectives: The primary objective of this study was to determine the attitudes of nurses towards the implementation of the MBFI in selected PHC facilities in the Makhuduthamaga Municipality, Limpopo province. Method: This study used a quantitative, descriptive design, and all respondents were conveniently sampled. A self-administered questionnaire was used to collect data. One-hundred and seventy-seven questionnaires were distributed, and 153 nurses responded and completed the questionnaire. The Statistical Package for Social Sciences version 23 was used to analyse data. Results: Results show that the majority of nurses (professional nurses [PNs] = 65, 78%; enrolled nurses [ENs] = 18, 72%; enrolled nursing auxiliaries [ENAs] = 23, 51%) had a positive attitude towards the MBFI strategy implementation as they agreed that it increased breastfeeding rates. Most PNs (n = 58, 70%) and ENs (n = 15, 60%) showed positive attitudes towards exclusive breastfeeding (EBF) as they agreed that it was the ideal feeding option for any child, and most ENAs (n = 38, 84%) showed a negative attitude as they disagreed that EBF was the ideal feeding option for any child. Conclusion: In this study, most PNs and ENs had a positive attitude in all the aspects that determined their attitudes towards MBFI strategy implementation. A concern is the fact that most ENAs showed negative attitudes in almost all the statements that were in line with the principles of MBFI, as they disagreed in most aspects. Therefore, this study recommends that on-going orientation and trainings should be offered to all nurses including ENAs to equip them with information that can assist in changing their attitudes towards MBFI implementation in PHC facilities.